2014
DOI: 10.1007/s11625-014-0263-7
|View full text |Cite
|
Sign up to set email alerts
|

The Maine Tidal Power Initiative: transdisciplinary sustainability science research for the responsible development of tidal power

Abstract: The Maine Tidal Power Initiative (MTPI), an interdisciplinary team of engineers, marine scientists, oceanographers, and social scientists, is using a transdisciplinary sustainability science approach to collect biophysical and social data necessary for understanding interactions between human and natural systems in the context of tidal power development in Maine. MTPI offers a unique opportunity to better understand how group structure and process influence outcomes in transdisciplinary sustainability science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It will be important to time such activities to avoid major fish migrations or presence of endangered and threatened species. Insight from this research has aided permitting for local and regional regulatory bodies, industry, and local stakeholders to make decisions regarding the social and legal acceptance of tidal power development and future device deployments [6]. Continued research is needed in the area of fish monitoring, along with other environmental assessments (e.g., mammals, birds, underwater noise), to allow this renewable energy source to develop into a sustainable, commercially viable market to further enable carbon emission mitigation of climate change effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be important to time such activities to avoid major fish migrations or presence of endangered and threatened species. Insight from this research has aided permitting for local and regional regulatory bodies, industry, and local stakeholders to make decisions regarding the social and legal acceptance of tidal power development and future device deployments [6]. Continued research is needed in the area of fish monitoring, along with other environmental assessments (e.g., mammals, birds, underwater noise), to allow this renewable energy source to develop into a sustainable, commercially viable market to further enable carbon emission mitigation of climate change effects.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the process of regulation and decision-making must happen simultaneously for the advancement of MHK technologies. The permitting process requires monitoring effects of MHK devices on the environment and adaptive management of that monitoring [6], particularly in the early stages of such new technology. Adaptive management proceeds best when used to guide decision-making, particularly as technologies move through different stages of development [7].…”
Section: Introductionmentioning
confidence: 99%
“…Securing funding for large interdisciplinary initiatives (~$1.5M annually, in this case) and the high level of commitment required to sustain and manage them were two of the challenges identified. The MTPI also found that student involvement can foster linkages between disciplinary teams and is critical to training the next generation of scientists and decisionmakers (Jansujwicz and Johnson 2015).…”
Section: A Case Study Of Marine Renewable Energymentioning
confidence: 99%
“…The WPSRC therefore used an engaged and participatory approach, as described below and in the online supplementary materials, to gather and share data with local communities. A strong baseline of trust that emerged from earlier MTPI interactions between the research team and individual community members contributed significantly to critical longterm working relationships (Jansujwicz and Johnson, 2015).…”
Section: Expanding Understanding Inmentioning
confidence: 99%
See 1 more Smart Citation